Q-dependence of the quasifree peak maximum position in ²Н(e,e')-reaction - Krasil’nikov, V.V.; Kuplennikov, E.L.; Levashov, I.A.; Ranyuk, Yu.N. (Вопросы атомной науки и техники, 2002)
The problem of the quasifree peak position of energy spectra at scattering electrons in inclusive ²H(e,e')- reaction is discussed. ε(q) dependence of the lightest deuterium nucleus is investigated. The fitting experimental points are realized by a 6-th power polynomial. It is proposed the new method of finding maxima of energy spectra and its errors at the polynomial fitting.